CHILDREN OF PRE-SCHOOL AGE DEVELOPMENT, EDUCATION AND MATURATION - Qushnazarov Farxod Norbo’tayevich; Maxkambayeva Ozoda Xusan qizi; Nazarova Ma’rifat Abduraim qizi (Journals Park Publishing, 2023)
This article describes the development, education and maturation of preschool children, which is the main focus of continuous education, and further development of learning abilities, which are the main foundation of their future.
Keywords: personality, weight, growth, formation, social development, activity, attitude, amount, upbringing, ability, environment, attention, thinking.